Random amplified polymorphic DNA (RAPD) finger printing in typing of leptospiral isolates* - VENKATESHA, M D; RAMADASS, P (The Indian Journal of Animal Sciences, 2014)
Random amplified polymorphic DNA (RAPD) profiles of 19 reference serovars belonging to 19 different serogroups of L. interrogans and 2 reference strains belonging to 2 serogroups of Leptospira biflexa were prepared. RAPD finger printing patterns of local isolates were compared with that of reference strains for their identification. The RAPD finger printing method of typing was simple, rapid and easy for typing leptospiral isolates.